Kinetics of papaya pectinesterase - Fayyaz, A.; Asbi, B.A.; Ghazali, H.M.; Che Man, Y.B.; Jinap, S. (Elsevier, 1995)
Purified papaya (Carica papaya L. var. exotica) pectinesterase (EC 3.1.1.11) was investigated for its activity as a function of NaCl, pH and temperature, and determination of its kinetic parameters. The activity was linear up to 20 min with an enzyme concentration of up to 6.14 μg. Optimum activity was obtained with 0.25 m NaCl concentration and the optimum pH was found to be 8. The energy of activation of enzyme was 5690 cal mol-1. A Q10 of 1.29 was observed in the temperature range of 30-50 °C and the optimum temperature for the enzyme activity was 65 °C. The Km value for citrus pectin was 0.11 mg/ml, corresponding to a Vmax value of 730 μmole/min/mg protein. The turnover number was calculated as 23 360 mole/(mole.min). Enzyme activity was found to be inhibited by the addition of polygalacturonic acid, alginic acid and sucrose in the reaction mixture and their Ki values were calculated as 0.019 mg/ml, 0.17 mg/ml and 29%, respectively. Polygalacturonic acid was found to act as a competitive inhibitor whereas alginic acid and sucrose showed a competitive-non-competitive and uncompetitive type of inhibition, respectively.